(untitled) (REVISTA NODO, 2013)
The article proposes a meditation on art becoming a space for interaction, creation and transformation of different realms in which politics are a cornerstone in the constitution of subjectivities. Accordingly, it thinks about art as a scenario where all standpoints, perspectives and worldviews can converge, and graffiti can come into sight as an expression of politics, mainly, as a point of view repossessing local cultural knowledge out of artworks staged on Bogota’s public space. Finally, it argues if art forms such as graffiti have a chance at socializing and constructing memory as well.